2021
DOI: 10.3390/genes12050731
|View full text |Cite
|
Sign up to set email alerts
|

Modifier Genes in Microcephaly: A Report on WDR62, CEP63, RAD50 and PCNT Variants Exacerbating Disease Caused by Biallelic Mutations of ASPM and CENPJ

Abstract: Congenital microcephaly is the clinical presentation of significantly reduced head circumference at birth. It manifests as both non-syndromic—microcephaly primary hereditary (MCPH)—and syndromic forms and shows considerable inter- and intrafamilial variability. It has been hypothesized that additional genetic variants may be responsible for this variability, but data are sparse. We have conducted deep phenotyping and genotyping of five Pakistani multiplex families with either MCPH (n = 3) or Seckel syndrome (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Although the G-box domain does not interact directly with tubulin, previously reported primary microcephaly (MCPH6) missense mutations E1235V in the G-box is known to increase centriole length (MCPH6) (Bond et al , 2005; Kitagawa et al , 2011a) via an unknown mechanism. Recently, another primary microcephaly mutation in the G-box domain has been mapped, which substitutes aspartic acid at 1196 amino acid position with the uncharged asparagine (Makhdoom et al , 2021). However, the effect of D1196N mutation on CPAP function remains to be tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the G-box domain does not interact directly with tubulin, previously reported primary microcephaly (MCPH6) missense mutations E1235V in the G-box is known to increase centriole length (MCPH6) (Bond et al , 2005; Kitagawa et al , 2011a) via an unknown mechanism. Recently, another primary microcephaly mutation in the G-box domain has been mapped, which substitutes aspartic acid at 1196 amino acid position with the uncharged asparagine (Makhdoom et al , 2021). However, the effect of D1196N mutation on CPAP function remains to be tested.…”
Section: Resultsmentioning
confidence: 99%
“…Specific mutations separating these two functions of CPAP would be a powerful tool to investigate mechanisms dictating this cross-talk between the centriole size and length. Recently another microcephaly mutation has been mapped in the G-box of CPAP, which resulted in missense mutation D1196N (Makhdoom et al , 2021). However, it is unknown how this would affect CPAP function and lead to microcephaly.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple transcript variants of this gene encoding different isoforms have been found. Therefore, this gene regulates the cell proliferation cycle, and the disorder caused by its high expression may cause the cell to eventually become cancerous (39,40). A previous study reported ASPM's cancer-promoting effects but did not confirm its status as an oncogene.…”
Section: Discussionmentioning
confidence: 98%
“…ASPM is the most frequently mutated gene in autosomal recessive PMs. Since the identification of the first patients [ 6 ], 861 individuals from 390 families carrying 210 different biallelic variants spread over the gene have been reported (for synthesis, see [ 50 , 51 ] and more recently [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]). Approximately 55% of published cases were of Pakistani origin.…”
Section: Aspm Wdr62 and Dynei...mentioning
confidence: 99%
“…A high proportion of this group of patients comes from consanguineous families. It remains unclear whether ASPM mutations alone cause epilepsy without MCD or whether additional variants in other PM- or epilepsy-causing genes exacerbate the phenotype, as shown by Duerincks et al and Makhdoom [ 62 , 66 ], underlying variabilities between patients or siblings. Finally, although this question remains unaddressed, the loss of normal excitatory–inhibitory neuronal balance in the cerebral cortex of patients carrying ASPM mutations may also explain the high rate of epilepsy in patients without MCD.…”
Section: Aspm Wdr62 and Dynei...mentioning
confidence: 99%